Penerapan Aplikasi Games Anatomi Model Drill And Practice untuk Meningkatkan Pemahaman Siswa di Sekolah Ramah Inklusi - Yunis Aprianti; Muhammad Rifki; Andi Prastowo; Sigit Prasetyo (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
Science lessons, especially biology, cannot be studied easily, one of which is material about the human digestive system. This material is complicated because the digestive organs work in the body so an appropriate learning model is needed. This research uses a Quantitative Drill and Practice Model approach based on audiovisuals and anatomical games applications to increase children's understanding in Yogyakarta inclusion-friendly elementary schools. The aim of this research is to increase students' understanding of the human digestive system material. The results show a significant increase in understanding as seen from the post-test results, including children with special needs (ABK) who also saw an increase, but for ABK students with ADHD (Attention Deficit Hyperactivity Disorder) and Multiple Disability (Down Syndrome and Physically Impaired) they have not been able to adapt to their classmates. so there is still a real need for special assistance/individual education and learning methods that are tailored to their level of needs. Educators are expected to be able to innovate using various media and learning models, such as using anatomy games applications with a drill and practice model.